Ethical theory and business - Arnold, Denis Gordon; Beauchamp, Tom L.; Bowie, Norman E., 1942- (New York : Cambridge University Press, 2019)
'For forty years, successive editions of Ethical Theory and Business have helped to define the field of business ethics. The 10th edition reflects the current, multidisciplinary nature of the field by explicitly embracing a variety of perspectives on business ethics, including philosophy, management, and legal studies. Chapters integrate theoretical readings, case studies, and summaries of key legal cases to guide students to a rich understanding of business ethics, corporate responsibility, and sustainability. The 10th edition has been entirely updated, ensuring that students are exposed to key ethical questions in the current business environment. New chapters cover the ethics of IT, ethical markets, and ethical management and leadership. Coverage includes climate change, sustainability, international business ethics, sexual harassment, diversity, and LGBTQ discrimination. New case studies draw students directly into recent business ethics controversies, such as sexual harassment at Fox News, consumer fraud at Wells Fargo, and business practices at Uber'--
'Ethical Theory and Business Tenth edition For forty years, successive editions of Ethical Theory and Business have helped to define the field of business ethics. The tenth edition reflects the current, multidisciplinary nature of the field by explicitly embracing a variety of perspectives on business ethics, including philosophy, management, and legal studies. Chapters integrate theoretical readings, case studies, and summaries of key legal cases to guide students to a rich understanding of business ethics, corporate responsibility, and sustainability. The tenth edition has been entirely updated, ensuring that students are exposed to key ethical questions in the current business environment. New chapters cover the ethics of IT, ethical markets, and ethical management and leadership. Coverage includes climate change, sustainability, international business ethics, sexual harassment, diversity, and LGBTQ discrimination. New case studies draw students directly into recent business ethics controversies, such as sexual harassment at Fox News, consumer fraud at Wells Fargo, and business practices at Uber'--
Machine generated contents note: Preface; 1. Ethical theory and business practice; 2. The rights and responsibilities of employees; 3. Managing, leading and governing; 4. Diversity and discrimination in the workplace; 5. Corporate social responsibility; 6. Ethics and information technology; 7. Marketing ethics; 8. Environmental sustainability; 9. Ethical issues in international business; 10. Ethical markets; 11. Economic justice.
Revised edition of Ethical theory and business, 2013.
Includes index.
Buku bacaan asas prasiswazah 2023/2024 Fakulti Ekonomi Pengurusan.
Keywords: Business ethics -- United States; Business ethics -- United States -- Case studies; Industries -- Social aspects -- United States; Industries -- Social aspects -- United States -- Case studies; Commercial crimes -- United States -- Cases; Consumer protection -- Law and legislation -- United States -- Cases